2011
DOI: 10.1603/en11027
|View full text |Cite
|
Sign up to set email alerts
|

Interaction BetweenUroplata girardi(Coleoptera: Chrysomelidae) andOphiomyia camarae(Diptera: Agromyzidae) on a Shared HostLantana camara(Verbenaceae)

Abstract: Multiple releases of insect agents intended to target a single plant pest species could result in competitive interactions that in turn might affect the community structure of the phytophagous insects. Two leaf-feeding biological control agents, Uroplata girardi Pic (Coleoptera: Chrysomelidae) and Ophiomyia camarae Spencer (Dipetera: Agromyzidae), were released against the weed Lantana camara L. (Verbenaceae) in South Africa in the 1970s and 2001, respectively. Since the population explosion of O. camarae in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Therefore, it is likely that the exclusion trials by cages might have prevented other factors that inflict damage on the uncaged plants such as exposure to wind, sun, dryness, and raindrop intensity. Our results together with those reported by April et al (2011) support the notion that the decline in the population density of U. girardi in KZN Province (Heystek 2006) is due to co-infestation by both agents which has a negative effect on U. girardi and a minor effect on O. camarae populations. April et al (2011) found that colonization of L. camara by both U. girardi and O. camarae reduced the population density of U. girardi, with the infestation level by the beetle averaging 9% per plant when combined with O. camarae, compared with 29% per plant when confined alone.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, it is likely that the exclusion trials by cages might have prevented other factors that inflict damage on the uncaged plants such as exposure to wind, sun, dryness, and raindrop intensity. Our results together with those reported by April et al (2011) support the notion that the decline in the population density of U. girardi in KZN Province (Heystek 2006) is due to co-infestation by both agents which has a negative effect on U. girardi and a minor effect on O. camarae populations. April et al (2011) found that colonization of L. camara by both U. girardi and O. camarae reduced the population density of U. girardi, with the infestation level by the beetle averaging 9% per plant when combined with O. camarae, compared with 29% per plant when confined alone.…”
Section: Discussionsupporting
confidence: 90%
“…Our results together with those reported by April et al (2011) support the notion that the decline in the population density of U. girardi in KZN Province (Heystek 2006) is due to co-infestation by both agents which has a negative effect on U. girardi and a minor effect on O. camarae populations. April et al (2011) found that colonization of L. camara by both U. girardi and O. camarae reduced the population density of U. girardi, with the infestation level by the beetle averaging 9% per plant when combined with O. camarae, compared with 29% per plant when confined alone. Similarly, field surveys in KZN indicated that U. girardi abundance levels ranged from 25 to 50% of infested leaves per plant prior to O. camarae release (Baars and Heystek 2003), and this declined to 2 to 7.5% four years after the release of the leafminer (April et al 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations